Vision and goal-directed movement neurobehavioral perspectives - Elliott, Digby 1950-; Khan, Michael A. 1966- (Human Kinetics, 2010)
To interact with the environment, an individual must code, store and translate spatial information into the appropriate motor commands. Working from this premise, this book discusses how visual perception, attention and memory are linked to the processes of movement. It is suitable for motor control and motor learning researchers, and students